Pentingnya Pendidikan Karakter pada Generasi Milenial di Era Digital - Aulia Arma Putri; Maya Nurantika; Siti Tiara Maulia (Journal on Education, 2023)
Character education itself was previously only imposed on two subjects, namely religious subjects and PKN, especially those related to the morals and character of students. Character education is the cultivation and development of positive character values ​​for students so that students have a good personality in accordance with the norms that apply in schools and in society. Implementation of character education in schools, habituation of students to good behavior needs to be supported by the example of teachers and principals (principals), along with all the elements that exist in the school. The research method used in this study is a literature review or literature study. Which contains the theories used related to the problems in this study. As for this research, the formulation of the problem is to find out "The Importance of Character Education in the Millennial Generation in the Digital Age". Where the millennial generation is a generation that is quite literate about the development of information technology. Where this generation has creative character, confidence and connected. Advances in information technology become their lifestyle. At this time, if you look at the current developments, there are many children who use technology for entertainment and lack of morals and socially unfavorable results in society due to wrong use of technology. Therefore, character education is of course very much needed to form a generation of good quality by fostering a sense of responsible attitude in using all aspects of technological development in today's digital era.